From An Economic Perspective, Lessons the Kurdistan Region Can Learn from South Korea? - Ramyar Ismael Jamal (QALAAI ZANIST JOURNAL, 2022)
This article discusses the lessons that the Kurdistan region can learn from South Korea from an economic perspective. The Kurdistan region of Iraq had gone through numerous economic obstacles and is still going through. The region like the rest of Iraq largely depends on oil revenues. It is yet to effectively take the advantage of other economic resources such as industrialization, agriculture and tourism. It has plans to utilize industrial and agricultural sources but not real steps have been taken. There are still tens of thousands of unemployed young graduates, lack of sounding administrative structure, and promotion of employees have stopped for few years. This article reveals the steps South Korea had taken to improve its economy from Education, Industrial and Agricultural points of view. Compare and contrasts are shown in the literature review part between the Kurdistan region and South Korea. Findings in the article include the Kurdistan region to boost its human capital, take the advantage of technology, avoid having oil as a single economic resource, and utilize its agricultural sector as well as industrialization. It is recommended for researchers interested in the area to conduct inquiry on what type of industrialization should the Kurdistan region engage in, and what agricultural products its territory is ready for.